INTERDISCIPLINARY TEACHING OF RUSSIAN LANGUAGE AND LITERATURE IN A NON-PHILOLOGICAL UNIVERSITY (American Journal of Interdisciplinary Research and Development, 2026)
The contemporary transformation of higher education requires a reconsideration of the role of language and literature disciplines in non-philological universities, where the traditional model of subject transmission is no longer sufficient to meet the demands of academic mobility, professional communication, and multicultural interaction. In this context, Russian language and literature courses acquire a renewed methodological significance because they function not merely as carriers of linguistic norms or literary knowledge, but as instruments for shaping the student’s cognitive culture, ethical worldview, interpretive maturity, dialogic competence, and ability to construct professionally meaningful speech in complex social settings. The present study develops and tests an interdisciplinary competence-based model for teaching Russian language and literature to students of a non-philological institution, with special attention to the agrarian university environment, where language training must interact with professional vocabulary, scientific discourse, humanitarian reflection, and the formation of personal communicative responsibility.